The role of traditions, culture and history in the development of Malaysian garden identity - Kaboudarahangi, Mina; Mohd Shariff, Mustafa Kamal; Mohd Tahir, Osman (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Globalization is fast transforming our world into one uniform and featureless place. Accordingly, the problem of national identity is a critical involving many developing nations. In this relation, Malaysia has recognized a clear vision for creating an exclusive national identity through the development of its landscapes and gardens. The country has always been proud of her natural environment and cultural heritage. However, the identity of its own Malaysian gardens is still unclear. This study aimed at identifying the importance of creating such an identity for Malaysia as a nation with unique traditions, culture, and history. The research employed the analysis of existing literatures on the subject as well as conducting interviews and supported by site observations. These lead to the recommendation of a framework for the design and creation of Malaysian gardens.